PERAN RADIO KOMUNITAS PEKKA JAYA DALAM PEMBERDAYAAN PEREMPUAN DI SUBANG JAWA BARAT - Farid Hamid; Ahmad Mulyana; Emilia Bassar (Universitas Mercu Buana, 2016)
Community radio is an alternative media channel for a community that does not get voice in the mainstream media. The purpose of this research is to know the role of Pekka Jaya community radio in Subang West Java in empowering women. The results showed that the presence of Pekka Jaya Subang Community Radio represented women's struggle against gender injustice. This radio plays a role in women's empowerment. Radio management is given entirely to women. This makes women learn independently in making decisions. At the same time also increase the capacity of women themselves. Pekka Jaya community radio in all the contents of the program is always oriented in the empowerment of women. By presenting specific topics about women, providing information and enriching women's insights.Community radio is an alternative media channel for a community that does not get voice in the mainstream media. The purpose of this research is to know the role of Pekka Jaya community radio in Subang West Java in empowering women. The results showed that the presence of Pekka Jaya Subang Community Radio represented women's struggle against gender injustice. This radio plays a role in women's empowerment. Radio management is given entirely to women. This makes women learn independently in making decisions. At the same time also increase the capacity of women themselves. Pekka Jaya community radio in all the contents of the program is always oriented in the empowerment of women. By presenting specific topics about women, providing information and enriching women's insights.Community radio is an alternative media channel for a community that does not get voice in the mainstream media. The purpose of this research is to know the role of Pekka Jaya community radio in Subang West Java in empowering women. The results showed that the presence of Pekka Jaya Subang Community Radio represented women's struggle against gender injustice. This radio plays a role in women's empowerment. Radio management is given entirely to women. This makes women learn independently in making decisions. At the same time also increase the capacity of women themselves. Pekka Jaya community radio in all the contents of the program is always oriented in the empowerment of women. By presenting specific topics about women, providing information and enriching women's insights. Radio komunitas merupakan saluran media alternatif bagi suatu komunitas yang tidak mendapatkan suara di media arus utama. Tujuan Penelitian ini adalah untuk mengetaahui peran radio komunitas Pekka Jaya di Subang Jawa Barat dalam memberdayakan perempuan. Hasil penelitian menunjukkan bahwa keberadaan Radio Komunitas Pekka Jaya Subang merepresentasikan perjuangan perempuan dalam melawan ketidakadilan gender. Radio ini berperan dalam pemberdayaan perempuan. Pengelolaan radio diberikan sepenuhnya kepada perempuan. Hal ini menjadikan perempuan belajar mandiri dalam mengambil keputusan. Sekaligus juga meningkatkan kapasitas perempuan itu sendiri. Radio komunitas Pekka Jaya dalam seluruh isi programnya selalu berorientasi dalam pemberdayaan perempuan. Dengan menyajikan topik‐topik yang spesifik tentang perempuan, memberikan informasi dan memperkaya wawasan kaum perempuan.